Microscopy methods in nanomaterials characterization - Thomas, Sabu; Thomas, Raju; Zachariah, Ajesh K.; Mishra, Raghvendra Kumar (Micro & nano technologies series, 2017)
Microscopy Methods in Nanomaterials Characterization fills an important gap in the literature with a detailed look at microscopic and X-ray based characterization of nanomaterials. These microscopic techniques are used for the determination of surface morphology and the dispersion characteristics of nanomaterials. This book deals with the detailed discussion of these aspects, and will provide the reader with a fundamental understanding of morphological tools, such as instrumentation, sample preparation and different kinds of analyses, etc. In addition, it covers the latest developments and trends morphological characterization using a variety of microscopes. Materials scientists, materials engineers and scientists in related disciplines, including chemistry and physics, will find this to be a detailed, method-orientated guide to microscopy methods of nanocharacterization.--Provided by publisher.